Nutritive assessment of four local herbal plants as animal feed supplements - Hamzah, Siti Fatimah; Alimon, Abdul Razak; Yaakub, Halimatun (Malaysian Society of Animal Production, 2017)
Many local herbal plants are generally rich in secondary metabolites and contain high amount of essential nutrients. A study was conducted to evaluate the antioxidant content and antimicrobial activities of 4 selected herbal plants: Andrographis paniculata (Hempedu Bumi), Orthosiphon stamineus (Misai Kucing), Euphorbia hirta (Ara Tanah) and Boreria latifolia (Boreria) that are widely available in Malaysia. Proximate analysis, phyto-chemical determination and in vitro technique were used to evaluate nutritive value of the herbal plants. Fatty acid profile and 2,2-diphenyl-1-picrylhydrazyl (DDPH) free radical scavenging activity were also explored. A. paniculata had the highest content of crude protein (18.13±0.18%), calcium (11.92±1.66%), sapon in (18.73±1.13%) and flavonoids (1.25±0.21%). while, E. hirta contained highest tannin (0.24±0.007%), phenol (0.02±0.004%) and antioxidant content (9.22±0.02%). For antimicrobial activity, E. hirta, A. paniculata and O. stamineus methanol extracts at 500 mg/ml concentration showed moderate antimicrobial activities. The methanol extracts of all herbal plants exhibited stronger antimicrobial activities against the test pathogens compared to the herbal water extracts. Among the 4 local herbal plants examined, A. paniculata contained the lowest total saturated fatty acids (26.53±0.19 g/100g FAME) and highest unsaturated fatty acids (73.47±0.19 g/100g FAME) and E. hirta had the highest total gas production (49.10±8.97ml), rate of gas production (2.05±0.37 ml/h). All herbal plants studied have their own potential as animal feed supplements.